Penggunaan Elemen Penghangat Cairan Intravena dengan Lampu Penghangat terhadap Shivering Pasca Operatif - I Made Sukarja; I Made Mertha (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2013)
The study aims to compare the effectiveness of the use of intravenous fluids heating element and heating lamps for post operative shivering. Methods of pre-experimental research studies (static group camparison/posttest design). The sample consisted of 20 people divided into the two group: group of intravenous fluids heating element and heating lamps group. The result of the treatment group heating element intravenous fluids, the time required to stop shivering average of 32,5 minutes, and the treatment group heating lamp until the shivering stops takes an average 50,4 minutes. In the Mann Whitney test, the value of p=0.000. It means that there are differences in effectiveness between the use of intravenous fluids heating elements and heating lamp in which the use of intravenous fluids heating elements are more effective than the use of heating lamps to overcome shivering in patient post operative.